The Drosophila Enhancer of zeste gene encodes a chromosomal protein: examination of wild-type and mutant protein distribution. - Carrington, E.A.; Jones, R.S. (Development, 1996)
The Drosophila Enhancer of zeste [E(z)] gene is a member of the Polycomb-group and, as such, is involved in maintaining the transcriptional repression of the homeotic genes of the Antennapedia (ANT-C) and bithorax (BX-C) complexes. It has been proposed that Polycomb-group (Pc-G)-mediated silencing requires the formation of heteromeric protein complexes which modify the chromatin structure of target genes. We describe the in vivo distribution of the E(Z) protein and show it to be ubiquitously present in embryonic and larval nuclei. In salivary gland polytenized nuclei, the identifiable E(Z) chromosome binding sites are a subset of those described for other Polycomb-group proteins, suggesting that E(Z) may also participate in Polycomb-group complexes. E(Z) binds to chromosomes in a DNA sequence-dependent manner, as illustrated by the creation of a new E(Z)-binding site at the location of a P element reporter construct that previously has been shown to contain a Polycomb response element (PRE). We also present the sequences of one null and three temperature-sensitive E(z) alleles, describe the effects these mutations have on the in vivo distribution of E(Z) protein and discuss their implications concerning putative functional domains. Finally, we describe the effect a trithorax mutation has on E(Z) chromosome binding.